A field deployable electrochemical technique based on a novel rotating side disk electrode for the estimation of mercury in environmental and biological samples - Agarwal R.; Behari J.R.; Prakash R. (My University, 2025)
A field deployable electrochemical technique based on anodic stripping differential pulse voltammetry (ASDPV) with a novel side disk gold rotating electrode has been used for the quantification of mercury in natural water, industrial wastewater, thermal power plant lakes and urine samples. A simple, user-friendly and cost-effective technique has been developed for the estimation of mercury directly in the field and affected areas as following the World Health Organization (WHO) and Environmental Protection Agency (EPA) recommendation regarding the allowed limits of mercury. Estimation is carried out using a unique side disk gold electrode in mild acidic condition (2 - 3% HCl) of various samples without any pretreatment or digestion of the samples. Mercury was estimated without any interference in various samples over a broad range from 1 to 100 μg/l. Mercury is also estimated in human urine, as a possible marker for mercury toxicity in the human. ©2008 Dustri-Verlag Dr. K. Feistle.